ANALISIS FAKTOR EKSTERNAL KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI KELAS XI IPA SEMESTER I DI SMAN 2 TAMBANG PADA MASA PANDEMI COVID-19 T.A 2020/2021 - Rifka Pratiwi Hutapea; Sri Wulandari; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the external factors of students' learning difficulties in learning biology class XI IPA semester I during the pandemic. Descriptive research was conducted at SMA Negeri 2 Tambang in October 2021. Sampling used a purposive sampling technique, the sample in this study was 69 students. The instrument used in data collection is a closed questionnaire and an open questionnaire. Before being used the questionnaire had gone through the validity and reliability test stages. The results showed that the external factor of the highest student learning difficulties was in the family environment aspect with an average of 67.75, while the school environment aspect had an average of 57.24 in the medium category and the social environment aspect had an average of 66.66 in the high category.Key Words: Learning difficulties, Pandemic, Biology learning